2007
DOI: 10.1002/eji.200737118
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of leukocyte CXCR4 expression by sulfatide: An L‐selectin‐dependent pathway on CD4+ T cells

Abstract: CXCR4 plays significant roles in immune and inflammatory responses and is important for selective recruitment of leukocytes. We previously showed that CXCR4 surface expression of human lymphocytes was affected by sulfatide, an in vivo ligand for L-selectin. Increased CXCR4 expression was shown to promote biologically relevant functions such as integrin-dependent adhesion and transmigration. Here, we show that sulfatide-induced CXCR4 up-regulation also occurs on other leukocyte subsets in humans and mice. B cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Subsequently, staining with Annexin V and 7-AAD was also performed to detect early apoptotic (Annexin V The increase of CXCR4 on extravascular neutrophils M Yamada et al 312 lymphocytes. 20,21 We observed that the shedding of L-selectin, which is induced by L-selectin activation, occurred during the process of extravasation of neutrophils (Figure 6a-c). We also found that sulfatide, a natural ligand for L-selectin, induced the surface expression of CXCR4 on neutrophils isolated from mouse blood.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Subsequently, staining with Annexin V and 7-AAD was also performed to detect early apoptotic (Annexin V The increase of CXCR4 on extravascular neutrophils M Yamada et al 312 lymphocytes. 20,21 We observed that the shedding of L-selectin, which is induced by L-selectin activation, occurred during the process of extravasation of neutrophils (Figure 6a-c). We also found that sulfatide, a natural ligand for L-selectin, induced the surface expression of CXCR4 on neutrophils isolated from mouse blood.…”
Section: Discussionmentioning
confidence: 94%
“…We further examined the effects of CXCL12 on isolated neutrophils to evaluate how this chemokine contributes to neutrophil accumulation in the injured tissue. In our investigation of the mechanism underlying the increase in surface CXCR4 expression levels, we focused on L-selectin because previous reports have shown that the activation of L-selectin induced the expression of surface CXCR4 in both human and mouse lymphocytes; 20,21 furthermore, the shedding of L-selectin, which resulted from the activation of L-selectin by its ligands, 22 was observed in extravasated neutrophils in inflamed tissues of mice.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Ding et al (24) reported that activation through L-selectin enhanced the expression levels of CXCR4 thus providing a potential explanation for how L-selectin ligation may regulate chemotaxis. However, this L-selectin-dependent CXCR4 upregulation was subsequently shown to be specific only for CD4 + T cells (25). Although these studies support a role for L-selectin in influencing lymphocyte chemotaxis, the specific signaling pathways involved or the degree to which this response is chemokineand/or cell type-specific remains unknown.…”
mentioning
confidence: 96%
“…The chemokines MCP-1/CCL2, IL-8/CXCL8, SDF-1 ␣ / CXCL12, MIP-1 ␣ /CCL3, and MIP-1 ␤ /CCL4 bind selectively to sulfatide with the site overlapping the glycosaminoglycan-binding site of MCP-1/CCL2. They are involved in human immunodefi ciency virus (HIV)-1 infection, hematopoiesis, angiogenesis, embryonic development, tumor metastasis, and graft rejection ( 90,91 ). Sulfatide might function as a receptor of these chemokines.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Binding of L-selectin to sulfatide triggers upregulation of the expression of the chemokine coreceptor CXCR4 surface expression on surfaces of human leukocytes such as CD4 + T cells. Interaction of chemokine ligand 12 (CXCL12) with CXCR4 induces chemostasis for leukocytes ( 90 ). Sulfatide is thought to contribute to migration elevated compared with that in healthy subjects ( 103 ), although the CST level of hepatocarcinoma tissues is similar to that in normal controls ( 104 ).…”
Section: Hemostasis/thrombosismentioning
confidence: 99%